Intermediaries in agro-food networks in Turkey: How middlemen respond to transforming food market structures - Appel, Alexandra; Franz, Martin; Hassler, Markus (DIE ERDE – Journal of the Geographical Society of Berlin, 2014)
Traditional wholesale intermediaries in the fresh fruit and vegetable segment tend to get expendable in markets with an increasing demand for traceability and for the fulfilment of quality and hygiene standards. The demand for these specifications is usually induced by transnational retail corporations that enter new market environments. This is also the case for Turkey, where since 2010 trade with fresh fruit and vegetable products can be conducted outside wholesale markets. Dualistic structures in accordance with socio-economic realities have emerged and the reactions of intermediaries towards these transformations vary between strategies of resilience and reworking. Therefore completely new purchasing channels emerge, whereby at the same time long-established trading patterns remain important to supply all groups of the society. This article is based on interviews conducted in Turkey.